Pengalaman Karyawan Operasional PT Sam Sam dalam Mengelola Penghasilan Bulanan dan Stres Keuangan - William Wanseven Gulo; Enik Rahayu (Mahesa Research Center, 2026)
This article aims to describe the experiences of operational employees at PT Sam Sam in managing their monthly income and to understand the forms and meanings of financial stress they experience. The problem focuses on limited income, personal financial management practices, and their implications for employees’ psychological conditions and work experiences. To approach this issue, the study draws on theories of behavioral finance, financial literacy, and transactional stress. Data were collected through in-depth interviews with six operational employees who had a minimum of five years of work experience, supported by limited observation and document review, and analyzed qualitatively using thematic analysis. The findings indicate that employees’ monthly income management remains simple and primarily oriented toward meeting short-term basic needs, with limited formal financial planning and risk management. This condition contributes to the emergence of financial stress, which is perceived as psychological pressure arising from uncertainty in fulfilling family needs and coping with unexpected expenses. This study concludes that income management experiences and financial stress are closely interconnected and highlights the importance of enhancing employees’ financial management capacity as part of efforts to support employee well-being and sustainable work performance.